1985
DOI: 10.1161/01.cir.71.6.1121
|View full text |Cite
|
Sign up to set email alerts
|

Factors that determine recovery of left ventricular function after thrombolysis in patients with acute myocardial infarction.

Abstract: The coronary and ventricular angiograms of 47 patients with acute myocardial infarction in whom reperfusion was achieved by intracoronary streptokinase were quantitatively analyzed to determine the factors that affect recovery of regional left ventricular function after reperfusion. Hypokinesis in the infarct region was measured by the centerline method and expressed in terms of standard deviations (SDs) from normal. Severity of coronary artery stenosis was measured quantitatively. Hypokinesis showed more sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(29 citation statements)
references
References 36 publications
2
25
0
2
Order By: Relevance
“…Later phenomena manifested in the plasma time-concentration curve would be anticipated to reflect the (3-phase rate constant of disappearance and the impact of interactions between the activator and circulating inhibitors affecting clearance in vivo as well. As judged from comparisons of plasma time-concentration curves of wild-type t-PA and five different species of t-PA (deglycosylated wild-type t-PA and genetically engineered variants [1][2][3][4], prolongation of the a-phase of clearance was associated with alterations of plasma time-concentration curves after intramuscular injections resulting in higher and more sustained early peaks.…”
Section: Discussionmentioning
confidence: 99%
“…Later phenomena manifested in the plasma time-concentration curve would be anticipated to reflect the (3-phase rate constant of disappearance and the impact of interactions between the activator and circulating inhibitors affecting clearance in vivo as well. As judged from comparisons of plasma time-concentration curves of wild-type t-PA and five different species of t-PA (deglycosylated wild-type t-PA and genetically engineered variants [1][2][3][4], prolongation of the a-phase of clearance was associated with alterations of plasma time-concentration curves after intramuscular injections resulting in higher and more sustained early peaks.…”
Section: Discussionmentioning
confidence: 99%
“…In reperfused myocardium, the persistence of a reduced flow across a high grade residual stenosis could cause persistent ischaemia or hibernation and limit functional recovery [44,45] . In our study, we elected to revascularize all patients exhibiting significant residual stenosis, in an attempt to reduce the effects of residual ischaemia on left ventricular function.…”
Section: Role Of Revascularizationmentioning
confidence: 99%
“…[1][2][3][4] Some investigators consider that viability seems to be more frequently present in patients with a rather preserved left ventricular (LV) function following AMI, 1 while others have suggested that those with more compromised function are more likely to improve over time. [2][3][4] In the present study, we attempted to gain further insight into the relationship between the predischarge status of LV function and the changes observed at 1 year in patients with a first anterior ST-elevation AMI following conventional management. Moreover, we also investigated the role of predischarge isotopic ventriculography with a low-dose dobutamine test (DBT) in predicting changes in LV ejection fraction (LVEF), regional contractility score (RCS), and LV end-diastolic volume index (EDVI) at 1 year.…”
Section: Introductionmentioning
confidence: 99%